OP05 Simulation and the future nurse a collaborative approach. (July 2019) - Woodhall, Nicola; Barker, Andrew; Ferguson, Wendy
Abstract : Aim: To meet the criterion of the 2018 Standards framework for nursing and midwifery education which require an increase in simulation education and partnership working. To use a simulated environment to explore the management of risk in a safe, supportive environment. To explore the evidence that deep learning occurs at the interactive interface. 1 Objectives: To explore the impact human factors and a person's frame of reference can have on decision making and dynamic risk assessment processes. To expand on existing knowledge in a safe space promoting confidence surrounding decision making and impact on patient care. To develop partnership working in order to replicate clinical environments and draw upon expertise across the educational field. To create a hypothetical authentic representation of reality. 2 Summary of work undertaken: Irvine and Martin 3 explore the move from practising and learning new skills on patients in a clinical environment to simulation-based training and found it critical to building bridges to real world experience. Educators should offer contextual procedural skills training, using scaffolding and authentication to accelerate learning while striving to ensure authenticity and fidelity within scenarios. With this in mind a highly authentic simulated environment was created. Students were immersed in a scenario recreating a home environment littered with risk. The students explored the room after being given a patient handover. This project had two initial pilots. Firstly, second year students were given prompt sheets which led them to categorise risks and think about escalation and record keeping. The second pilot worked with third year students who were given no prompts due to the stage and level of experience of their academic studies. Following 15 minutes in the simulated environment, students were given 10 minutes to decide the level of risk of each element and the escalation and documentation required. A 40 minute debrief followed, which utilised an advocacy and inquiry model, where students were asked to explore how their frame of reference and human factors may have affected their risk assessment process. Following feedback from students, facilitators and observers from all fields the success of the pilots conducted with Mental Health Nursing Students only was agreed. Future simulations will be conducted using an interdisciplinary approach allowing learning with, from, and about all fields of healthcare. Impact on practice: Students receiving simulation as opposed to lecture demonstrate improved technical ability and theory retention; showing a shift from acquisition of facts to knowledge integration. 4 Strengthening of partnership working, which is of vital importance if we are to continue to develop and enhance patient care. Nurses working in varying post reg or post qualification roles can enrich the teaching scenarios and using a mutli educational approach, promoting how nurses/healthcare practitioners will work once in a full-time clinical environment. Increase in student confidence which will lead to a confident future work force. The intention is to give confidence underpinned by evidence that shows how to deal with potentially emergency situations in a safe environment taught is supportive and encourages debate and feedback. References: Prout S, Lin I, Nattabi, B, and Green C. 'I could never have learned this in a lecture': Transformative learning in rural health education. Advances in Health Sciences Education 2014;19(2):147–159. doi:10.1007/s10459-013-9467-3 Bland AJ, Topping A, Wood B. A Concept Analysis of Simulation as a Learning Strategy in the Education of Undergraduate Nursing Students. Nurse Education Today 2010;31:664–670. DOI:10.1016/j.nedt.2010.10.013 Irvine S, Martin J. Bridging the gap: From simulation to clinical practice. The Clinical Teacher 2014;11(2):94–98. doi:10.1111/tct.12060 Ramsingh, D., Alexander, B., Le, K., Williams, W., Canales, C., and Cannesson, M. Comparison of the didactic lecture with the simulation/model approach for the teaching of a novel perioperative ultrasound curriculum to anesthesiology residents. Journal of Clinical Anesthesia 2014;26(6):443. doi:10.1016/j.jclinane.2014.01.018 Nursing and Midwifery council. (2018). Realising professionalism: Standards for education and training. Available at: https://www.nmc.org.uk/standards-for-education-and-training/standards-framework-for-nursing-and-midwifery-education Accessed: 11 June 2019.